2013
DOI: 10.1186/1756-0500-6-161
|View full text |Cite
|
Sign up to set email alerts
|

Service evaluation of weight outcomes as a function of initial BMI in 34,271 adults referred to a primary care/commercial weight management partnership scheme

Abstract: BackgroundIt is not clear if behaviour change programmes are more or less effective for weight management in people with high BMIs than for those who are moderately overweight. An earlier service evaluation reported on the rate and extent of weight loss in a primary care/commercial weight management organisation partnership scheme, in 34,271 patients were referred by their health care professionals to a UK commercial weight management organisation, Slimming World for 12 weekly sessions. This project updated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Sixty percent of this population had a BMI over 30 kg/m 2 suggesting that lifestyle interventions can work on a large scale in populations who are overweight and obese at least over a period of 3 months. The analysis of weight outcomes by BMI groups suggested that lifestyle interventions can be as effective in individuals with higher BMIs as well as for those who are moderately overweight during their first 3 months attendance which is in accordance with previous analysis [ 27 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Sixty percent of this population had a BMI over 30 kg/m 2 suggesting that lifestyle interventions can work on a large scale in populations who are overweight and obese at least over a period of 3 months. The analysis of weight outcomes by BMI groups suggested that lifestyle interventions can be as effective in individuals with higher BMIs as well as for those who are moderately overweight during their first 3 months attendance which is in accordance with previous analysis [ 27 ].…”
Section: Discussionsupporting
confidence: 89%
“…[ 14 ]. Slimming World already delivers an effective, national scale infrastructure for weight loss, including networks of local classes, 4000 group facilitators (Consultants), written, online and multi-media resources, eating plans and evidence based behaviour change approaches [ 22 , 27 , 28 , 61 ]. The present data set provides an important addition to the UK evidence base for commercial weight management programmes, particularly as this represents the majority of participants accessing such services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings suggest that these community programmes help people with higher BMIs to lose weight. A large audit of Slimming World found similar findings, in that percentage weight loss was similar across categories of BMI (27). This audit did not specifically consider participants with a BMI >40 kg/m 2 compared to lower BMI categories.…”
Section: Comparison With Existing Literaturementioning
confidence: 69%
“…Slimming World (SW), as a member of East Midlands Platform for Health and Wellbeing, is the largest commercial weight management organisation in the UK, based on group attendances, serving over 800,000 members each week. SW has also been operating referral schemes (SW on referral) to the NHS since 2000, with its effectiveness appropriately reviewed in the scientific literature (Lavin et al, 2006;Stubbs et al, 2011Stubbs et al, , 2013. However, little is known on the effectiveness of referral to community groups via the workplace.…”
Section: Introductionmentioning
confidence: 99%